Strategy and Sustainability of Ecotourism Villages in the Buleleng Regency - I Gusti Ayu Purnamawati; Gede Adi Yuniarta; I Gusti Bagus Baskara Nugraha (Accounting Department, School of Business and Management - Universitas Kristen Petra, 2024)
Analysis of personal motivation, use of digital information, and green tourism branding in Buleleng Regency is very important for the sustainability of the ecotourism villages that are starting to be developed. This research used a quantitative approach with a population of 16,521 people with respondent selection using purposive sampling to obtain 236 people. The primary data type was by giving questionnaires (Likert scale) to village heads, traditional Kelian, official Kelian, homestay owners, tourism awareness group (pokdarwis) heads, tourists, and village communities. All data was analyzed using WarpPLS 7.0. This research reveals that personal motivation, the use of digital information, and branding, influence the sustainability of ecotourism villages in Buleleng Regency. The results of this research are in line with the theory of planned behavior and attribution which explains individual motivation and the factors determining the success of a business, including technological support in the use of accounting information, while promotion is an external attribution. This research can provide information for the tourism village actors in Buleleng Regency regarding the promotion and management of tourism which should be in synergy with traditional villages and official villages. All community roles cannot be separated from collaboration between stakeholders who have a big responsibility in expanding the village towards independence.